Intermediate sulfidation epithermal mineralization of No. 4 anomaly of Golojeh deposit (N. Zanjan) based on mineralography, alteration and ore fluid geochemistry features - Behzad Mehrab; Nafise Chaghaneh; Ebrahim Tale Fazel (Journal of Economic Geology, 2014)
The base (Cu–Pb–Zn) and precious metals (Ag±Au) mineralization at the No. 4 anomaly of Golojeh deposit occurred in volcanic and sub–volcanic Eocene–Oligocene host rocks, in the central part of the Tarom–Hashtjin zone. Basic to intermediate volcanic, volcaniclastic and sub–volcanic rocks are dominated in the area and include andesite, basaltic andesite, trachy-andesite, dacite and tuff with affinity to sub–alkaline to high–potassic calc–alkaline series. The mineralization in the area with average grade of Au (0.15 ppm), Ag (0.24%), Cu (0.6%), Zn (4%) and Pb (6%) occurred in two major NW–SE trending quartz–sulfide veins (A and B) with crustiform, breccia, vein–veinlet and open-space filling structure and texture. The sulfide content varies from 5 to 60% and is dominated by galena, sphalerite, chalcopyrite and pyrite. SEM studies indicated presence of Ag (0.47 to 0.66 wt.%) and Cd (0.33 to 0.72 wt.%) in galena and Fe (0.23 wt.%) in sphalerite. Hydrothermal alteration of phyllic (quartz–sericite–pyrite), argillic (quartz–illite/muscovite) and silicification are related to mineralization. Correlation coefficient of metal pairs of Cd–Zn (0.86), Cd–Pb (0.82), Pb–Ag (0.80), Au–Ag (0.75), Pb–Zn (0.70) and Cd–Bi (0.74) was recorded in the quartz–sulfide ore–bearing veins. Microthermometric studies on two phases liquid–vapor fluid inclusions in ore–bearing veins, shows homogenization temperature to liquid (Thlv→l) in the range of 223 to 287°C and salinity of 6.5 to 17 wt.% NaCl eq. (quartz-hosted) and homogenization temperature ranging from 175 to 244°C and salinity from 1.5 to 12 wt.% NaCl eq. (sphaerite-hosted). First ice–melting temperature (Tmf) ranges of fluid inclusion in sphalerite-hosted of quartz–sulfide ore–bearing veins were recorded between −23 and −18°C in NaCl–H2O system. Vein–breccia and crustified structure and texture, presence of illite/muscovite alteration assemblage accompanied by high contents of galena, sphalerite and minor chalcopyrite and tennantite, low to moderate temperature and salinity of ore-bearing fluid, low depth of mineralization and Fe–bearing sphalerite features at the No. 4 anomaly of Golojeh deposit, are similar to those of intermediate sulfidation (IS) epithermal base and precious metals vein–type deposit that probably might be related to Cu–Au porphyry system in depth.